New approach for modeling processes of doping redistribution during oxidization - Berezhansky, Volodymyr (Видавництво Львівської політехніки, 2012)
Redistribution of doping during diffusive-oxidizing processes is simulated. The optimal technological conditions of diffusive oxidizing processes is determined.
Keywords: quasilinear process; The Deale-Grove’s model; interphase border; numerical methods; diffusive-oxidizing processes